ANALISIS KONDISI EKOSISTEM TERUMBU KARANG DI KAWASAN PESISIR KOTA PALOPO - Muhammad Bibin; Fenny Hasanuddin; Ani Ardian (Universitas Bengkulu, 2021)
Damage to coral reefs on the coast of Palopo City will certainly threaten their productivity. Therefore, it is essential to use and manage coral reefs in the coastal area of Palopo City by applying the principles of a conservation area management system through integration, participation, and multi-stakeholders. This study aims to analyze the level of damage and the causes of coral reef damage and formulate a strategic model for managing coral reef ecosystems in the coastal area of Palopo City. Methods of data analysis using analysis of coral reef conditions, analysis of patterns of damage to coral reefs, and analysis of the processes' hierarchy. The percentage of live coral cover in the coastal area of Palopo City is categorized as damaged / sour with a percentage value (0–24.9%). One of the causes of damage to coral reefs in the coastal area of Palopo City is the existence of community activities that have damaged coral reefs in the past, such as fishing using non-environmentally friendly fishing gear such as fish bombs and potassium. The highest level of damage to coral reefs was at station 1, with a depth of 4 meters and the percentage of the mortality index was 82.07%. Simultaneously, the lowest level of damage is at station two at a depth of 4 meters, with a mortality index percentage of 69.73%. The first priority strategy in managing coral reef ecosystems on the coast of Palopo City is to determine the zoning of coastal areas. The second priority is coordination between stakeholders. The third priority is the preparation of regional regulations regarding the use of coral reef ecosystems. The fourth priority is to increase training programs for fishing communities.